Development of a Group Guidance Service Model Based on Segulaha Cultural Values to Improve the Character of Junior High School Students - Andi Agustan Arifin; Syamsul Bachri Thalib; Kamaruddin Hasan (Journal of Educational Science and Technology (EST), 2024)
This research is a development research which aims to find out: (1) Description of the need for a group guidance service model based on segulaha cultural values in improving the character of junior high school students in Ternate City, (b) Design of a group guidance service model based on segulaha cultural values in improving the character of junior high school students in Ternate City, (c) Validity, practicality and effectiveness of the segulaha cultural values-based group guidance service model in improving the character of junior high school students in Ternate City. The type of research is Research and Development with the ADDIE model. Data collection was carried out by using questionnaires, observations, feasibility and practicality assessment sheets. The data obtained was then analyzed using qualitative and quantitative statistics. The results of the research show that a group counselling service model is needed in improving character education based on cultural values. The model designs created are outlined in model books and guidebooks for group guidance services based on cultural values to improve student character. The model developed is valid, feasible and practical to be continued in supporting group guidance services based on cultural values as well as improving the character of junior high school students. The results of the analysis of the effectiveness of the segulaha cultural values-based group guidance service model in improving the character of junior high school students were very effective. This is based on the results of the pretest and posttest which have increased.